2018
DOI: 10.4314/tjpr.v17i9.6
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of bacoside A on hypertrophic scar formation by downregulation of TGF-β1

Abstract: Purpose:To determine the anti-scarring property of bacoside A (BA) in a rabbit model of post-burns hypertrophic scar (HS). Methods: A total of 16 healthy male rabbits were divided into four groups (4 rabbits/group). The rabbits were subjected to full-thickness burn wound by placing a 10-mm brass rod at 90 ºC on their ears for 20 s, and were untreated (HS group). The remaining rabbits also underwent HS process but were topically treated daily with 0.2, 0.4 or 0.6 % BA gel (HS + 0.2, 0.4, and 0.6 % BA groups) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Therefore, in the development of pharmaceuticals for the suppression of scar formation, Bacoside-A has the potential for use. [336] Endocrine Effects Bacopa extract (200 mg/kg orally) has increased the thyroid hormone T 4 by 41% in mice, while T 3 has not been stimulated, implying that the extract is capable of directly stimulating the synthesis and/or release of T 4 at the glandular level without affecting the conversion of T 4 to T 3 . [337] Besides this, in hypothyroid and euthyroid animals, ethanolic extract of the whole plant increased both T 4 and T 3 and decreased TSH level, which revealed that Bacopa's thyrogenic activity is not only localized in the thyroid gland, but that certain central or peripheral actions may be taken by the herb.…”
Section: Wound Healing Aptitudementioning
confidence: 99%
“…Therefore, in the development of pharmaceuticals for the suppression of scar formation, Bacoside-A has the potential for use. [336] Endocrine Effects Bacopa extract (200 mg/kg orally) has increased the thyroid hormone T 4 by 41% in mice, while T 3 has not been stimulated, implying that the extract is capable of directly stimulating the synthesis and/or release of T 4 at the glandular level without affecting the conversion of T 4 to T 3 . [337] Besides this, in hypothyroid and euthyroid animals, ethanolic extract of the whole plant increased both T 4 and T 3 and decreased TSH level, which revealed that Bacopa's thyrogenic activity is not only localized in the thyroid gland, but that certain central or peripheral actions may be taken by the herb.…”
Section: Wound Healing Aptitudementioning
confidence: 99%
“…Another in vivo study was performed in order to evaluate the effect of bacosides on the wound healing caused by burns in rabbits; after 28 days of topical application of a bacoside A extract, the levels of collagen, hydroxyproline and hexosamine decreased, as did the size of the wound. Authors hypothesized that the healing effect of bacoside A is due to a complex mechanism of action that involves: (i) changing the structure of collagen fibers; (ii) upregulation or downregulation of beta-1 growth factor and metalloproteinase-1 matrix transformation [112].…”
Section: Bacosidesmentioning
confidence: 99%
“…Bacopa monnieri has been reported to moderate the secretion of collagen type I and III, improve collagen fibre organization and remodeling. 11,12 Acalypa indica was found to exhibit angiogenic activity by enhancing Vascular Endothelial Growth Factor (VEGF) and up-regulate selected pro-wound healing cytokines. [13][14][15] Topical application of Calotropis gigantea on wound was reported to modulate type I collagen secretion and reorganization during wound healing.…”
Section: Introductionmentioning
confidence: 99%